Effects of pharmacological doses of 2-deoxyglucose on plasma catecholamines and glucose levels in patients with schizophrenia - Elman, Igor; Rott, David; Green, Alan I.; Langleben, Daniel D.; Lukas, Scott E.; Goldstein, David S.; Breier, Alan (Psychopharmacologia, 2004)
Several lines of evidence suggest that the pathophysiology of schizophrenia may be associated with altered noradrenergic and glucoregulatory function. The aim of this study was to investigate these alterations during a perturbed homeostatic state. Fifteen patients with schizophrenia and 13 healthy individuals were given a glucose deprivation challenge through administration of pharmacological doses of 2-deoxyglucose (2DG; 40 mg/kg), and their plasma was assayed over the next 60 min for concentrations of norepinephrine (NE), the intraneuronal NE metabolite dihydroxyphenylglycol (DHPG), epinephrine and glucose. 2DG induced significant increases in plasma NE, epinephrine and glucose levels in both groups with significantly greater NE and glucose increments in patients than in controls. For DHPG, 2DG produced increases in patients and decreases in the control subjects. NE responses correlated positively and significantly with the DHPG and glucose responses in schizophrenics, but not in controls. These findings suggest that patients with schizophrenia have exaggerated NE and glucose responses to an acute metabolic perturbation.